Th role of counselling to reduce parental fears and anxiety about newborn screening for sickle cell disease in Northern Ghana - Enyonam Duah; Samuel T. Chatio; Lucy O. Ababio; Nicola Lister; Olufolake Egbujo; Kwaku Marfo; Isaac Odame; Patrick Ansah (BMC Public Health)
Abstract Introduction In Ghana, about 15,000 newborn children are diagnosed to have sickle cell disease (SCD) annually. Previous studies have demonstrated that while neonatal screening coupled with early intervention reduces SCD-related morbidity and mortality, only 50–70% of screened-positive children have been successfully followed-up to receive healthcare. Gazelle point-of-care testing (POCT) device with high specificity and sensitivity may be more easily integrated into existing immunization programs in rural settings, to improve follow-up rates. This study explored views of community members and healthcare workers about the role of counselling to reduce parental fears and anxiety about newborn screening for SCD in rural Northern Ghana. Methods This study used qualitative research approach where 16 focus group discussions and 19 in-depth interviews were conducted with participants between April and June 2022. Purposive sampling technique was used to select participants for the interviews. The interviews were recorded with consent of participants, transcribed and coded into themes using QSR Nvivo 12 software before thematic analysis. Results Participants saw the need for counselling services to be provided to participants in the planned SCD screening program. They believed that effective counselling could help parents take appropriate strategies to manage children diagnosed with SCD and improve their health status. Furthermore, healthcare workers, mothers and opinion leaders held that counsellors could offer words of encouragement to parents to reduce their anxiety and fears during the screening especially, those whose children could be tested positive. They however suggested various strategies such as adequate training and positive behaviour of counsellors to ensure effective counselling process during the SCD screening program. Conclusion Although counselling has been described as a key component in the planned SCD screening program, adequate training to improve knowledge, counselling skills as well as positive attitude of counsellors towards parents could enhance the effectiveness of counselling services offered.